Makrootoczenie w kreowaniu międzynarodowej pozycji podmiotów gospodarczych - Styś, Stanisław (Macroenvironment in Creating International Position of Entrepreneurs, 2007)
While adapting the Polish economy to market economy rules, there are still dilemmas of enterpreneurs and public authorities. Both of them represent different point of view concerning mutual relations or relative independence in the name of market liberty and building competitiveness. The author holds the view that there should be interdependence of enterpreneurs and public authorities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 9-14